2005
DOI: 10.1021/cm051582s
|View full text |Cite
|
Sign up to set email alerts
|

Cyanate Ester/Polyhedral Oligomeric Silsesquioxane (POSS) Nanocomposites:  Synthesis and Characterization

Abstract: Cyanate ester (PT-15, Lonza Corp.) composites containing the blended polyhedral oligomeric silsesquioxane (POSS), TriSilanolPhenyl-POSS (C 42 H 38 O 12 Si 7 ), were prepared containing PT-15/POSS 99/1, 97/3, 95/5, 90/10, and 85/15 w/w ratios. The composites were characterized by FT-TR, X-ray diffraction (XRD), small-angle neutron scattering (SANS), scanning electron microscopy (SEM), X-ray energy dispersive spectroscopy (X-EDS), transmission electron microscopy (TEM), dynamic mechanical thermal analysis (DMTA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 57 publications
(53 reference statements)
2
94
0
Order By: Relevance
“…Nanocomposites with silica nanoparticles have been reported to display increased mechanical properties [8,9] such as modulus, tensile, flexural and impact strength up to a certain silica content (e.g. 2.5% [10]) and decreased mechanical properties thereafter, improved fracture toughness [11] and better thermal stability [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocomposites with silica nanoparticles have been reported to display increased mechanical properties [8,9] such as modulus, tensile, flexural and impact strength up to a certain silica content (e.g. 2.5% [10]) and decreased mechanical properties thereafter, improved fracture toughness [11] and better thermal stability [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Dispersed silica nanoparticles have been used as a curing agent in an epoxy system in the presence of magnesium chloride, acting as a catalyst, to yield a silica-epoxy nanocomposite [20]. Incorporation of silica nanoparticles and silicates has been reported to raise the glass transition temperature, T g , of the resulting nanocomposite (cyanate ester composites [9], vinyl ester composites [1], epoxy composites [13,21]) but also to reduce Tg (clay-biobased epoxy nanocomposites [18]). …”
Section: Introductionmentioning
confidence: 99%
“…With regard to polyhedral oligomeric silsesquioxane (POSS)/ polymer composites, only several pieces of literature report the flexural properties. Liang's group prepared POSS/cyanate ester nanocomposites, and found that the flexural modulus of the nanocomposite with 3 wt% POSS is about 15% higher than that of neat cyanate ester resin, while the composite has the similar flexural strength as the resin does [26]. Li's group also reported similar results in the POSS/ epoxy nanocomposites [27].…”
Section: Mechanical Properties Ofmentioning
confidence: 92%
“…In Ash's same paper [43], which reported increases of the strain-to-failure for alumina nanoparticle/PMMA composites, the T g of the nanocomposites decreased by 25 °C compare to neat PMMA at certain nanoparticle loadings. Other researchers reported an increase in the T g of nanocomposites with increasing nanoparticle loading [45][46][47]. The effect of nanoparticles on the T g of nanocomposite is far more complex than the simple increase/decrease trend with particle loading.…”
Section: Nanoparticles For Composite Enhancementmentioning
confidence: 99%